2000
DOI: 10.1016/s0167-4889(00)00018-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-kinase inhibitors, Wortmannin or LY294002, inhibited accumulation of p21 protein after γ-irradiation by stabilization of the protein

Abstract: Expression of the cyclin kinase inhibitor, p21, is regulated both transcriptionally and posttranscriptionally by the ubiquitin-proteasome degradation pathway. Recently, we reported that DNA damage is required for efficient p21 expression by demonstrating that enhanced p21 mRNA expression induced by DNA damage results in increased p21 protein, but enhanced p21 mRNA without DNA damage does not. In addition, we demonstrated that DNA damage suppressed the ubiquitination of p21. In this study, we analyze the link b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Our study shows that at 10 mM, the compound alone has no intrinsic growth inhibition properties but it significantly potentiates the effect of radiation in CH1 human ovarian cancer cells. The radiosensitisation effect of this compound has previously been shown to compare very well with results that have been reported for LY294002 and wortmannin (Rosenzweig et al, 1997;Fukuchi et al, 2000;Kim et al, 2002). We examined the effect of drug exposure on the relatively radiosensitive CH1 human ovarian carcinoma cell line.…”
Section: Discussionmentioning
confidence: 53%
“…Our study shows that at 10 mM, the compound alone has no intrinsic growth inhibition properties but it significantly potentiates the effect of radiation in CH1 human ovarian cancer cells. The radiosensitisation effect of this compound has previously been shown to compare very well with results that have been reported for LY294002 and wortmannin (Rosenzweig et al, 1997;Fukuchi et al, 2000;Kim et al, 2002). We examined the effect of drug exposure on the relatively radiosensitive CH1 human ovarian carcinoma cell line.…”
Section: Discussionmentioning
confidence: 53%
“…Here, we asked if Stat3 was involved in the upregulation of Mcl-1 in U87 cells that were treated with LY294002 for 24 h. Accordingly, U87 cells were treated with LY294002 for varying lengths of time and the DNA-binding activity of Stat3 was determined by EMSA. We noted with surprise that in the absence of activated PI3K-AKT, the in vitro DNA-binding activity of Stat3 in U87 cells was significantly increased between 15 and 24 h (Figure 4a), This observation was confirmed by treating U87 cells with another PI3K inhibitor Wartmannin (Sonoda et al, 1999;Fukuchi et al, 2000) (Figure 4a). Similar results were obtained with D54 cells (Figure 4b).…”
Section: Of Three Independent Determinationsmentioning
confidence: 68%
“…PI3K-AKT pathway provides survival signals in a variety of normal and cancer cells (Datta et al, 1999). As shown in Figure 2b, U87 cells that contained persistently activated AKT began to undergo apoptosis when exposed to LY294002, a potent inhibitor of PI3K (Fukuchi et al, 2000) for 6 h and AKT phosphorylation was completely blocked after 3 h. These data clearly indicate that PI3K-AKT pathway provides survival signal in U87 cells. We have previously shown that activated Stat3 suppresses spontaneous apoptosis of U251 cells (Rahaman et al, 2002).…”
Section: Egfr Provides Major Survival Signals Through Both Stat3 and mentioning
confidence: 73%
“…These ®ndings pointed to defective Atm function as a possible cause of radiosensitization. Despite reduced p53 induction there were only minor di erences in p21 WAF1 induction, perhaps because of p53-and ATM-independent in¯uences on p21 (Wouters et al, 1999;Fukuchi et al, 2000).…”
Section: Discussionmentioning
confidence: 92%